EFEKTIVITAS ADSORBEN ARANG AKTIF KULIT DURIAN (Durio Zibethinus) DAN WAKTU KONTAK TERHADAP PENURUNAN KONSENTRASI PEWARNA NAPHTOL LIMBAH CAIR BATIK - Wike Maylani; Ismiyati Ismiyati; Yustinah Yustinah (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
This study aims to analyze the characteristics of activated charcoal from durian shells and to determine the absorption capacity of activated charcoal from durian shells which acts as an adsorbent in reducing the concentration of naphtol dye in batik wastewater based on mass variations of activated charchoal (0,5%; 1%; 1,5%; 2%; dan 2,5%b/v) and variation of contact time (0, 25, 50, 75, and 100 in minutes). The characteristic results of activated charcoal from durian shells include a yield content 86,6%; moisture content of 9%; ash content of 13.3%; iodine absorption of 526.635 mg/g; the surface area using the methylene blue method is 456.24 m2/g and the SEM (Scanning Electron Microscope) test to determine the surface morphology of the activated charcoal. Based on the effect of the mass of activated charcoal from durian shells and contact time, the best results are obtained on a mass of 2,5%b/v of activated charchoal on durian shells and a contact time of t5 minutes to reduce the concentration of naphtol dye. In these parameters, the final concentration of naphtol dye from batik wastewater is obtained of 52,64 mg/l with a reduction percentage of naphtol dye of 79,52%.